Study on the organization of pedagogical work in a municipal public school: Evidence of the forms of control and its political determination - Marieta Gouvêa de Oliveira Penna; Alda Junqueira Marin (Arizona State University, 2020)
This article investigates aspects of the school pedagogical work, observing the signification, processes, dynamics, and relations. We also investigate hierarchical relations, task divisions, and the occurrence, or absence, of collective work. Our focus is the institutional relations between teachers and the administration team. The investigation was accomplished in a municipal public school in the metropolitan area of São Paulo, where children attend at Early Childhood, from 3-5 years old, followed by the initial years of Basic Education. Data were collected by means of semi-structured interviews with the school principal, the coordinator, and two teachers engaged in the school proposal. Ball's studies are considered, focusing on the power relations and the diversity of goals that guide the pedagogical work. Lima's perspective of microanalytical investigation of the school and Weber's forms of domination are also adopted. The analysis of the strategies established by the administration team showed that the school under investigation works as both a bureaucratic organization and an organized anarchy. Efforts are carried out for the establishment of a shared administration, involving all the school agents. We also noted the existence of teachers' resistance concerning the proposals issued by the administrative team, demonstrating ideological disputes and disputes for interests present in its daily routine.